MICROCLIMATE DATA MEASURED AT THE YUKIDORI VALLEY, LANGHOVDE, ANTARCTICA IN 1988-1989 - OHTANI, Shuji; KANDA, Hiroshi; INO, Yoshio (National Institute of Polar Research, 1990)
P(論文) departmental bulletin paper